2011
DOI: 10.2217/pgs.10.208
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sensitive, Specific and Rapid Pharmacogenomic test for the Prediction of Abacavir Hypersensitivity Reaction: HLA-B*57:01 Detection by Real-Time PCR

Abstract: We provided a detailed characterization of a novel HLA-B*57:01 screening test, which can be easily implemented by those laboratories already involved in the detection of viral load and virus genotyping. Original submitted 26 October 2010; Revision submitted 13 December 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…13,14 One of the obstacles for screening for HLA-B*5701 in developing countries is laboratory cost. Low cost techniques, such as polymerase chain reaction sequence-specific primer-based genotyping, may make screening feasible in resource-limited settings 15 Whether or not HLA-B*5701 screening has been performed, clinical training on early detection of the clinical symptoms of abacavir hypersensitivity, especially in the first 6 weeks of treatment, should be emphasized. Abacavir should be immediately discontinued in any patient who develops clinical signs and symptoms consistent with hypersensitivity and rechallenge is contraindicated.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 One of the obstacles for screening for HLA-B*5701 in developing countries is laboratory cost. Low cost techniques, such as polymerase chain reaction sequence-specific primer-based genotyping, may make screening feasible in resource-limited settings 15 Whether or not HLA-B*5701 screening has been performed, clinical training on early detection of the clinical symptoms of abacavir hypersensitivity, especially in the first 6 weeks of treatment, should be emphasized. Abacavir should be immediately discontinued in any patient who develops clinical signs and symptoms consistent with hypersensitivity and rechallenge is contraindicated.…”
Section: Discussionmentioning
confidence: 99%
“…The Prospective Random Evaluation of DNA Screening in a Clinical Trial (PREDICT‐1) has shown that ABC HSR is strongly associated with HLA‐B*57:01 . Such a finding has been confirmed by various studies, which lead to the implementation of recommendation guidelines by the US Food and Drug Administration (FDA) and international HIV treatment guidelines for HLA‐B*57:01 screening before initiating treatment with ABC …”
Section: What Is Known and Objectivesmentioning
confidence: 87%
“…The qPCR was based on the protocol described by Dello-Russo et al, that was adapted to avoid the necessity of the initial HLA-B PCR [ 16 ]. This assay targets the exon 2 (Primers 193F, 319R and HLA 57:01 exon 2 probe; S2 Table ) and exon 3 (Primers 345F, 419R and HLAB57:01 exon 3 probe; S2 Table ) region of the HLA-B*57 : 01 allele.…”
Section: Methodsmentioning
confidence: 99%
“…This method has been further optimized by subsequent capillary electrophoresis, enhancing the sensitivity of the assay [ 15 ]. More recently, new assays were developed for HLA-B*57 : 01 typing on a qPCR platform [ 11 , 16 , 17 ]. This enables detection of primer specificity through differentiating Cq values by SYBR Green quantitative (q)PCR [ 16 ], or analysis of allele specific PCR by high resolution melting [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation